First discovery of Sarcocornia perennis subsp. alpini (Chenopodiaceae) in Algeria with note on the distribution of Sarcocornia perennis subsp. perennis - Bensouna, Amel; Sari-Ali, Amel; Babali, Brahim (Phytotaxa, 2020)
Sarcocornia perennis subsp. alpini (Chenopodiaceae) is recorded in Algeria (coastal region of Rachgoun , NW-Algeria) for the first time. A description of the species is provided as well as a morphological comparison with other closely related species which occur in the same rich and threatened biotope (a conservation policy is highly recommended).